1998
DOI: 10.1007/bf02464049
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and diversity of microfungi in three coastal beaches of Mexico

Abstract: The abundance and diversity of species of microfungi was investigated on the beaches of Delfines, Km 24 Veracruz-Alvarado Highway, and El Coco, located on the coasts of the Caribbean Sea, Gulf of Mexico, and the Pacific Ocean, respectively. On each beach a sample composed of sand, subtidal wood or washed-up detritus with moist sand was collected. The samples were analyzed by three different methods, resulting in a total of 1,160 occurrences that fluctuated between 340 and 441 occurrences/sample. The number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
(21 reference statements)
1
11
0
2
Order By: Relevance
“…Some of the micromycetes found in this work had already been reported in Mexico, such as: Aspergillus spp (sand beach) (Gonzalez et al 1998; sediments; Scopulariopsis spp (Alias and Jones 2000) from mangroves (Kohlmeyer 1968), and plant material (Jones et al 2009;Singh et al 2012) and Peniophora spp from marine sponges (Bonugli-Santos et al 2016). Phialosimplex sclerotialis and P. caninus have recently been reported in deep marine sediments (Singh et al …”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Some of the micromycetes found in this work had already been reported in Mexico, such as: Aspergillus spp (sand beach) (Gonzalez et al 1998; sediments; Scopulariopsis spp (Alias and Jones 2000) from mangroves (Kohlmeyer 1968), and plant material (Jones et al 2009;Singh et al 2012) and Peniophora spp from marine sponges (Bonugli-Santos et al 2016). Phialosimplex sclerotialis and P. caninus have recently been reported in deep marine sediments (Singh et al …”
Section: Discussionsupporting
confidence: 63%
“…In Mexico there have been a few studies of marine fungi, including fungal isolates from beach sand, sea foam, floating wood and mangrove (Gonzalez et al 1998;Gonzalez et al 2000;Gonzalez et al 2001); however, none has been reported from marine sediments under 40 m deep as we did. The aim of this study was to isolate and identify marine halotolerant fungi from sediments of the Southern California Gulf.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…To quantify microbial abundance and diversity in the rhizosphere soil of Z. qatarense in saline and nonsaline habitats, data were analysed according to statistical methods as outlined by Mandeel et al (1995) and Gonzalez et al (1998). The abundance of species (n) is expressed as the number of individual occurrences of a species.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing-based studies are rare, except Arfi et al (2012) who investigated the anoxic mangrove sediments of Saint Vincent Bay, and revealed that Agaricomycetes was the dominant fungal class. As a result, insufficient information on the fungal community in the sediment of intertidal ecosystems is hindering our understanding of their ecological functions (González et al, 1998; Sallenave-Namont et al, 2000; Rämä et al, 2014). …”
Section: Introductionmentioning
confidence: 99%